Diagnóstico multitemporal sobre las dinámicas urbanas entre carreras 33 - 38 y calles 45 - 51a cabecera del llano. - Africano Serrano, Sergio Elías; Angarita Pabón, Luis Gustavo (Universidad Antonio Nariño, 2025)
Propia